PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MEDIA AUDIO VISUAL DI KELAS V SDN 04 BATU BALANG - Becky Sonata; Zulfani Sesmiarni; Rodi Rodi (CV. ADIBA ASIHA AMIRA, 2024)
This classroom action research aims to determine whether the use of audio- visual media can improve the learning outcomes of students in class V SDN 04 Batu Balang. This research is based on the low learning outcomes of students, where conventional learning methods are considered less effective in helping students understand the material optimally. Audio-visual media is considered effective because it involves more of the students' senses, which can help them understand the subject matter better. This research uses the classroom action method (CAR) with two cycles, where each cycle includes planning, implementation, observation, and reflection. The data collected includes the results of student tests before and after the application of audio-visual media, as well as observations of their learning activities during the learning process. The results of the study showed a significant increase in student learning outcomes after the application of audio-visual media. In addition, students became more active and motivated in the learning process. The use of audio-visual media has proven effective in improving the learning outcomes of students in class V SDN 04 Batu Balang. Therefore, this media is recommended to be applied in the learning process for other subjects that require a better understanding of concepts. This study recommends that teachers use audio-visual media more often in learning to improve students' motivation and understanding of the material being taught.